2012
DOI: 10.4028/www.scientific.net/amm.184-185.1323
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition Effects of Wood Light Induced Discoloration Coating with Water-Based Acrylic Varnish

Abstract: In this paper, we used water-based acrylic varnish to coat poplar and pinus sylvestris veneer, discussed the inhibition effects of veneer light induced discoloration with two coating ways which were paint coating and film covering. The result showed that, after paint coating or film covering, the lightness aberration of veneer ΔL* and chromatism ΔE*ab were significantly reduced. The inhibition rate of veneer light induced discoloration with film covering was 7.88% higher than that with paint coating, reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In an analysing of colour changes, Söğütlü and Döngel (2009) observed that when cellulosic, synthetic, polyurethane and acid-catalysed varnishes were applied to oak, east beech, chestnut and Scotch pine woods, the most colour changes occurred in synthetic varnished samples. Liu et al (2012) stated that poplar and scots pine (Pinus sylvestris L.) veneer samples coated with water-based acrylic varnish. They found that the lightness aberration of veneer (ΔL*) and chromatism (ΔE* ab) significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In an analysing of colour changes, Söğütlü and Döngel (2009) observed that when cellulosic, synthetic, polyurethane and acid-catalysed varnishes were applied to oak, east beech, chestnut and Scotch pine woods, the most colour changes occurred in synthetic varnished samples. Liu et al (2012) stated that poplar and scots pine (Pinus sylvestris L.) veneer samples coated with water-based acrylic varnish. They found that the lightness aberration of veneer (ΔL*) and chromatism (ΔE* ab) significantly reduced.…”
Section: Introductionmentioning
confidence: 99%